Biphasic multiplex PCR based on bead array for high-throughput and sensitive authentication of meat products - Lingfeng Yan; Rong Cao; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Food Control, 2026)

Global ammonia (NH3) retrieval from the FY-3F satellite hyperspectral infrared atmospheric sounder and performance assessment - Zhili Deng; Yapeng Wang; Minqiang Zhou; Ling Gao; Lin Chen; Xifeng Cao; Lingfeng Zhang; Yuhan Jiang; Haiyang Dou; Xingying Zhang (Atmospheric Environment, 2026)

From waste to thermal regulator: Upcycling preservative-treated wood into multifunctional composite phase change materials for sustainable thermal management - Zhenxin Zhang; Yanan Dong; Lingfeng Kong; Phuocthoi Hoang; Xiaoqi Zhao; Jinzhen Cao (Journal of Cleaner Production, 2026)

Dynamic risk assessment and early warning for water inrush during the excavation of karst river-crossing tunnels - Zengguang Xu; Zimeng Chen; Weili Ma; Fan Zhang; Lingfeng Zhao; Cheng Cao; Junrui Chai; Fajian Jin (Carbonates and Evaporites, 2026)

Development of a high-throughput sensitive SB-PCR assay for rapid detection of laboratory-escaped antibiotic resistance genes - Lingfeng Yan; Shengnan Liu; Rong Cao; Azadeh Nilghaz; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Journal of Environmental Chemical Engineering, 2026)

A novel transformer-based CO2 retrieval framework incorporating prior constraint and hierarchical features injection: assessment of transferability for Tansat-2 - Lingfeng Zhang; Lu Zhang; Xingying Zhang; Tiantao Cheng; Xifeng Cao; Tongwen Li; Dongdong Liu; Yang Zhang; Yuhan Jiang; Ruohua Hu; Haiyang Dou; Lin Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Polyphthalocyanine-based nanostructure for sono-immunotherapy by reprogramming the tumor microenvironment and blocking immune checkpoint - Lingfeng Jiang; Jiawei Wang; Wenjun Liu; Xin Xie; Xiao Luo; Ling Tu; Liangqing Tang; Qing Zhang; Hongmei Yuan; Hanfeng Yang; Qi Li; Sujiao Cao; et al. (Chemical Engineering Journal, 2026)

Urban vegetation productivity under climate change and increasing urbanization: Insights from both urban-rural comparison and trend analysis for global cities - Jiuyi Chen; Bo Qiu; Weidong Guo; Xin Miao; Yipeng Cao; Zhihan Zhao; Siwen Zhao; Lingfeng Li; Yueyang Ni; Shihan Tang; Limei Yang (Urban Forestry & Urban Greening, 2025)

Correction: Divergent dominant physical processes of extreme heatwaves in northern and southern China - Yueyang Ni; Bo Qiu; Yipeng Cao; Xin Miao; Lingfeng Li; Jiuyi Chen; Siwen Zhao; Xiaohui Tian; Weidong Guo (Climate Dynamics, 2025)

Multi-scale analysis of six evapotranspiration products across China: Accuracy, uncertainty and spatiotemporal pattern - Lingfeng Zuo; Lei Zou; Jun Xia; Liping Zhang; Hui Cao; Dunxian She (Journal of Hydrology, 2025)

Divergent dominant physical processes of extreme heatwaves in northern and southern China - Yueyang Ni; Bo Qiu; Yipeng Cao; Xin Miao; Lingfeng Li; Jiuyi Chen; Siwen Zhao; Xiaohui Tian; Weidong Guo (Climate Dynamics, 2025)

The coupling of ultra-nano oxygenation and in-situ sediment remediation technology jointly promotes phosphorus enrichment and nitrogen removal - Lu Cao; Lingling Wan; Chunhui Xi; Zijun Zhou; Siyang Wang; Lingfeng Cao; Zhicheng Min; Xiankun Chen; Yiyong Zhou; Xiuyun Cao; Chunlei Song (Journal of Water Process Engineering, 2025)

Optimal balance of organic detritus and feed for fish growth and water quality improvement through regulating nutrients cycling - Lu Cao; Lingling Wan; Lingfeng Cao; Zhicheng Min; Yiyong Zhou; Xiuyun Cao; Chunlei Song (Environmental Research, 2024)

Influence of corrosion on seismic performance of steel beam-to-column connections - Yuelin Zhang; Cheng Fang; Wei Wang; Lingfeng Wu; Peng Cao (Engineering Structures, 2024)

Potential high-risk release sources of thallium and arsenic from surrounding rocks of a typical thallium and arsenic mining area in southwest China - Yanpei Du; Lingfeng Shi; Xinyan Cao; Fengqi Zhao; Pengjie Hu; Rongrong Ying; Shangyi Gu; Longhua Wu; Yongming Luo; Peter Christie (Science of The Total Environment, 2024)

Relationship between eutrophication and greenhouse gases emission in shallow freshwater lakes - Jingjie Zhang; Lingfeng Cao; Zhenghan Liu; Lingling Wan; Xiuyun Cao; Yiyong Zhou; Chunlei Song (Science of The Total Environment, 2024)

Valorization of straw biomass into lignin bio-ink, bacterial cellulose and activated nanocarbon through the trade-off alkali-catalyzed glycerol organosolv biorefinery - Lingfeng Long; Jinkang Chen; Yueqin Cao; Chen Huang; Shoushuai Feng; Hailin Yang; Dong Tian (Chemical Engineering Journal, 2024)

Overlooked fluorine deficiency in children of South and East China may be exacerbated by climate change: Evidence from the national assessment - Lingfeng Zhou; Weigang Liang; Yaobin Meng; Xiaoli Zhao; Fei Guo; Lingling Liu; Wenjing Li; Miaomiao Teng; Fanhao Song; Zhiqiang Cao; Yidong Mi; Qigen Lin; et al. (Journal of Cleaner Production, 2024)

Molecular-level insights into the heterogeneous variations and dynamic formation mechanism of leached dissolved organic matter during the photoaging of polystyrene microplastics - Fanhao Song; Tingting Li; Jin Hur; Quan Shi; Fengchang Wu; Wei He; Di Shi; Chen He; Lingfeng Zhou; Mingqi Ruan; Yuhan Cao (Water Research, 2023)

Surface display of major capsid protein on Bacillus subtilis spores against largemouth bass virus (LMBV) for oral administration - Quan Wang; Xia Liang; Yunshang Ning; Shijia Liu; Zengjian Liang; Zemiao Zhang; Yingjing Chen; Jinqiao Cao; Fubao Wang; Lingfeng Lan; Guangzhao Cheng; Youhua Huang; et al. (Fish & Shellfish Immunology, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

Metagenomic insights into feasibility of agricultural wastes on optimizing water quality and natural bait by regulating microbial loop - Lingling Wan; Lingfeng Cao; Chunlei Song; Xiuyun Cao; Yiyong Zhou (Environmental Research, 2023)

Review of construction methods for whole-cell computational models - Jingru Zhou; Xingcun Fan; Lingfeng Cao; Huijie Sun; Jianye Xia; XueFeng Yan (Systems Microbiology and Biomanufacturing, 2022)

Insights into fouling behavior in a novel anammox self-forming dynamic membrane bioreactor by the fluorescence EEM-PARAFAC analysis - Yijing Zhu; Lijuan Cao; Lingfeng Ni; Yayi Wang (Environmental Science and Pollution Research, 2020)

Molecular characterization and multiple infections of rotavirus, norovirus, sapovirus, astrovirus and adenovirus in outpatients with sporadic gastroenteritis in Shanghai, China, 2010–2011 - Lijuan Lu; Ran Jia; Huaqing Zhong; Menghua Xu; Liyun Su; Lingfeng Cao; Zuoquan Dong; Niuniu Dong; Jin Xu (Archives of Virology, 2015)

Molecular epidemiology of human calicivirus infections in children with acute diarrhea in Shanghai: a retrospective comparison between inpatients and outpatients treated between 2006 and 2011 - Lijuan Lu; Huaqing Zhong; Menghua Xu; Liyun Su; Lingfeng Cao; Niuniu Dong; Jin Xu (Archives of Virology, 2014)

Spatial and temporal distribution of nanoflagellates in the northern South China Sea - Bangqin Huang; Wenlu Lan; Zhenrui Cao; Minhan Dai; Lingfeng Huang; Nianzhi Jiao; Huasheng Hong (Hydrobiologia, 2008)